BMI mobility and obesity transitions among children in Ireland - David Madden (University College Dublin, UCD Centre for Economic Research, 2019)
This paper examines mobility and changes in Body Mass Index (BMI) for a sample of Irish children across three waves of the longitudinal Growing Up in Ireland dataset. Particular attention is paid to transitions across the key BMI thresholds of overweight and obesity. Analysis is carried out by gender and by maternal education. In general, the degree of mobility appears to be relatively limited although it is greater than for the mothers of the children over the same time period. There is relatively little variation by gender and maternal education apart from some indication of less mobility out of obesity for girls.
Keywords: I12; I14; I39; 330; Obesity; mobility; transitions